Short Communication: Application of bacteriocin from Lactobacillus plantarum SRCM 1 004 34 strain isolated from okara as a natural preservative in beef sausage - SALAM N. ARITONANG; ELLY ROZA; AFRIANI SANDRA (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Aritonang SN, Roza E, Sandra A. 2020. Short Communication: Application of bacteriocin from Lactobacillus plantarum SRCM 1 004 34 strain isolated from okara as a natural preservative in beef sausage. Biodiversitas 21: 2240-2243. Lactic Acid Bacteria (LAB) can be found in food and most of the LAB have beneficial effects for humans as potential probiotics. LAB isolated from okara (soy milk pulp) produces antimicrobial compounds called bacteriocins which can be used as natural preservatives in sausages. This study aims to determine the effectiveness of this bacteriocin from LAB as a natural preservative in sausages. The bacteriocin was isolated from Lactobacillus plantarum SRCM 1 004 34 strain isolated from Okara. Completely Randomized Design (CRD) was used in 4 X 4 factorial pattern by three replicates The first factor was the percentage addition of bacteriocin (B): 0% (B0), 0.3% (B1), 0.6% (B2) and 0.9% v/b (B3). The second factor was the length of sausage storage time at 4°C (L): 0 days (L0), 4 days (L1), 8 days (L2) and 12 days (L3). The observed variables were moisture content, protein, fat, pH, total aerobic bacteria, and sausage fatty acid profile. The results showed that the content of protein, fat, and the bacterial count was significantly influenced by the interaction of the percentage addition of bacteriocin and storage time. pH was significantly affected by bacteriocin dose and storage time but was not affected by the interaction of other factors. The moisture content of the sausage was significantly affected by storage time. The results of this study showed that sausages treated with 0.9% bacteriocin (B3) with a maximum storage time of 12 in the refrigerator was still safe to be consumed.